(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
Placed in the IP "Actors and Factors of The Microentorno of the Esquel Delegation of the Faculty of Economic Sciences of the Patagonia San Juan Bosco National University", this work arises in which a specific tool of market research is applied. Semantic Differential (DS). The purpose of DS is to measure the meaning that has a certain object or situation for people, seeking to grasp the affective meaning. In the present work, the students are consulted regarding the degree courses offered by our institution, seeking to specify the qualities related to the same discipline in relation to academic and labor aspects. Questions that we try to answer are: What is the valuation of the student of degree of Economic Sciences of the profession for which it is being formed and of the race that is taking? Are there differences in these ratings according to the height of the race in which you are? What is your perception of the characteristics of the chosen discipline and its professional responsibilities?.The qualifications that the students contribute spontaneously regarding the races that they are useful, practical, important and interesting. That the chosen race was dictated in the Faculty was one of the motivational factors that determined its permanence in Esquel, to carry out its university studies. The opinion of the Faculty as an institution, both for the students who are entering the different careers and for those who are finishing their courses, is of acceptance.